The constitutional treatment of the constitutional deficiency “diagnosis and treatments” study within the framework of the Iraqi constitution for the year2005 - Negemish, Basim; Adil, Musadaq (Journal of Legal Sciences, 2022)
Constitutions, no matter how divided and separated in the constitutional rules, the perception that there is a constitutional deficiency here or there in constitutional matters is inevitable, so the constituent authority cannot claim infallibility or negligence and is fortified in the circle of legislative deficiency.  Treated by modification and judicial interpretation.